Nightside Detection of a Large‐Scale Thermospheric Wave Generated by a Solar Eclipse. Issue 8 (24th April 2018) - Harding, B. J.; Drob, D. P.; Buriti, R. A.; Makela, J. J.
Abstract: The generation of a large‐scale wave in the upper atmosphere caused by a solar eclipse was first predicted in the 1970s, but the experimental evidence remains sparse and comprises mostly indirect observations. This study presents observations of the wind component of a large‐scale thermospheric wave generated by the 21 August 2017 total solar eclipse. In contrast with previous studies, the observations are made on the nightside, after the eclipse ended. A ground‐based interferometer located in northeastern Brazil is used to monitor the Doppler shift of the 630.0‐nm airglow emission, providing direct measurements of the wind and temperature in the thermosphere, where eclipse effects are expected to be the largest. A disturbance is seen in the zonal and meridional wind which is at or above the 90% significance level based on the measured 30‐day variability. These observations are compared with a first principles numerical model calculation from the Thermosphere‐Ionosphere‐Mesosphere‐Electrodynamics General Circulation Model, which predicted the propagation of a large‐scale wave well into the nightside. The modeled disturbance matches well the difference between the wind measurements and the 30‐day median, though the measured perturbation (∼60 m/s) is larger than the prediction (38 m/s) for the meridional wind. No clear evidence for the wave is seen in the temperature data, however. Plain Language Summary: Solar eclipses are natural experiments that allow us to test our models of the upper atmosphere. It has long been theorized that during a solar eclipse, the fast motion of the Moon's shadow across the Earth should cause a wave in the upper atmosphere, similar to the bow wave that develops in front of a boat. In contrast with the boat, which pushes water ahead of it, the cold atmosphere inside the shadow acts like a sinkhole that pulls the air ahead of it. In this paper, we report the first direct observations of the atmosphere moving in response to an eclipse, using data taken during and after the Great American eclipse on 21 August 2017. These observations match well the predictions made by a commonly used upper atmosphere model, in both the timing and size of the response. An interesting aspect of these observations is that they were made in Brazil, after the eclipse had ended, emphasizing the global nature of the eclipse response. This study is important because it provides direct evidence to support previous theoretical eclipse studies, and it furthers our confidence that our first principles models of the upper atmosphere are capturing the relevant physics. Key Points: Direct detection of the wind perturbation of a large‐scale wave generated by the 21 August 2017 total solar eclipse is presented Ground‐based observations are made on the nightside, after the eclipse forcing has subsided The measured wind perturbation agrees well with the TIME‐GCM first principles model, but the temperature measurement is inconclusive